A música como linguagem no processo de alfabetização científica nas aulas de química - Silveira, Miguel Luiz da (2019)
Among the sciences, chemistry stands out due to the various possibilities of addressing each topic, starting from a simple observation of an experiment or from the reading of nature itself, emerging the questions and the necessary intricacy for the production of scientific knowledge. Something that difficults the chemistry teaching is the way it is practiced. Excessively transmitted, not in a full context, resulting in does not consider the comprehension and the experience of the student. This dissertation was oriented by the use of music as an instrument of work and language in the process of scientific literacy in chemistry classes, so that there was a greater interest of students in learning this discipline and, consequently, promoted an improvement in quality of teaching and learning through the playful surroundings. Currently, it would be easier to list the environments where the music is not present. The modern smartphones are a potential educational tool in the teaching and learning processes when they have their teacher-oriented use. The use of active methodologies, where the student is the protagonist and the producer of his own knowledge, it confers a new dynamic to the process, always guided by the mediator-teacher, who also ends up assuming the role of an oriented-researcher of the educational process. The present work developed an educational sequence to teach the content of electrochemistry, using a playful methodology, with songs and/or parodies, accompanied by intricacy and contextualization considering the experiences of students. In sequence, the groups of students according to their musical preference produced unpublished music and/or musical parodies as products of this work, involving the key concepts of the electrochemical contents that were worked in the classroom, evidencing the process of scientific literacy according to Chassot and Miller.